Penyuluhan Fisioterapi Mengenai Stretching Exercise untuk Mengurangi Keluhan Low Back Pain (LBP) pada Karyawan Bening’s Clinic Pamekasan - Syamsa Liatis Zailia; Anita Faradilla Rahim (Lembaga Pengembangan Kinerja Dosen, 2025)
Introduction: Low back pain is one of the most common musculoskeletal disorders encountered in the work environment and is categorized as a disease caused by work activities. Methods: This study used health promotion counseling method on stretching exercise for low back pain (LBP). The counseling was held on March 15, 2025 at Bening's Clinic Pamekasan which is located on Jl. Trunojoyo no. 325-327, Pocok, Laden, Kec. Pamekasan, Pamekasan Regency, East Java. A total of 21 workers participated in this counseling. The promotional media used in this activity was a leaflet, and pre-test and post-test were applied as instruments to measure the effectiveness of the counseling. Results: The results of the evaluation of 21 participants showed that their understanding of Low Back Pain (LBP) and stretching exercise increased to 100%. Conclusion: Based on the results evaluation results, the counseling conducted at Bening's Clinic Pamekasan successfully increased participants' understanding of stretching exercise for low back pain (LBP).